2022
DOI: 10.1039/d2dt00130f
|View full text |Cite
|
Sign up to set email alerts
|

Pressure -induced changes in the persistent luminescence of Gd2.994Ce0.006Ga3Al2O12 and Gd2.964Ce0.006Dy0.03Ga3Al2O12 nanoceramics

Abstract: Pressure applied during sintering of the nanoceramics may enhance persistent luminescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In the manganites, a decrease in the crystallite size leads to a reduction in the magnetization [41] by a disruption of the long-range ferromagnetic interactions occurring in volume and especially in the surface layer of the crystallites. The decrease in the crystallite size was observed already by us [42,43], and is related to the decomposition of the surface layer of the nanocrystallite and decrease in the size of the core. Additionally, it can be observed that for the ceramics at high diffraction angles, the background strongly increases, this may be potentially related to the reflection mode of measurement made on non-parallel surfaces of the small pieces of the ceramics.…”
Section: Structure and Morphologymentioning
confidence: 56%
“…In the manganites, a decrease in the crystallite size leads to a reduction in the magnetization [41] by a disruption of the long-range ferromagnetic interactions occurring in volume and especially in the surface layer of the crystallites. The decrease in the crystallite size was observed already by us [42,43], and is related to the decomposition of the surface layer of the nanocrystallite and decrease in the size of the core. Additionally, it can be observed that for the ceramics at high diffraction angles, the background strongly increases, this may be potentially related to the reflection mode of measurement made on non-parallel surfaces of the small pieces of the ceramics.…”
Section: Structure and Morphologymentioning
confidence: 56%
“…These properties are critical for efficient light collection and detection. The synthesis conditions can affect the wavelength of emitted light, which in turn affects the choice of photodetectors used to capture the scintillation signals [7,[12][13][14][15]. The synthesis process can influence the mechanical integrity and stability of the scintillator material.…”
Section: Introductionmentioning
confidence: 99%